Improving the Mechanism of Countering Certain Types of Fraud in the Republic of Kazakhstan - TEMIRZHANOVA, Lyazzat А.; IMANGALIEV, Nurtai K.; SYZDYKOV, Almaz Zh.; ESHNAZAROV, Almaz A.; SAGYMBEKOV, Bakhytzhan Zh. (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The urgency of the problem stated in the article is due to the fact that the widespread digitalization of the economy leads to the fact that crimes such as theft and fraud are committed using computer tools and systems. According to statistics from Kazakhstan, as a result of fraud using computer technology, damage in the amount of more than 28 billion tenge was caused, of which individuals - 24.7 billion tenge, legal entities - 1.8 billion tenge and the state - more than 1 billion tenge. In this regard, the study touched upon issues of ensuring information security and countering cyber threats. The purpose of the article is to develop effective measures to prevent the commission of fraud with the use of information technology, since theft begins from cyber attacks on information systems. In this study, methods such as comparative legal analysis and expert evaluation were used. Amendments are proposed to the criminal legislation of the Republic of Kazakhstan regarding the jurisdiction of crimes, on the addition of qualifying signs, and on the need to adopt a new Law on real estate activity in the Republic of Kazakhstan. Amendments to the criminal law will have a positive effect on the ‘unloading’ of investigators of the internal affairs bodies, since the number of ordinary crimes related to their competence significantly exceeds the number of crimes in the sphere of economic activity. The adoption of a new law on real estate activity in the Republic of Kazakhstan will avoid the facts of re-registration of apartments for criminal purposes, the commission of fraud by realtors.